Integration of 4C Skills on Student Worksheets Prospective Professional Physics Teacher in West Sumatra - Natasya, Ziola; Festiyed, Festiyed; Asrizal, Asrizal (Jurnal Penelitian Pembelajaran Fisika, 2024)
The 21st century is an era full of challenges which requires the world community to improve the way they think, learn, work and live in the worldin order to keep up with the rapid progress of information technology. The aim of this research is to determine the extent of integration of 4C skills in student worksheets. This research uses a quantitative approach, with descriptive research type. The object of this research is a student worksheet on Light and Optical Instruments created by 10 prospective professional physics teachers at one of the state universities in West Sumatra. This research instrument is in the form of a questionnaire prepared based on the 4C skill indicators formulated by R.T. Kelley, etc. in the form of positive statements. Based on the analysis that has been carried out on student worksheets made by prospective professional physics teachers, it can be concluded that the content of 4C skills consisting of critical thinking skills is in the high category, while creative thinking skills, communication skills and collaboration skills are in the high category medium category. This research is expected to be able to provide information and an overview of the extent of the distribution of 4C skill content on student worksheets